الخطوات المناسبة عند الطريقة المباشرة والسمعية الشفهية لتدريس مهارة الكلام - Abdul Ghofir (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2018)
One of the objectives of teaching Arabic is to improve students' speaking skills. This purpose is to express the skill of speech and the way it is taught. In this case, the researcher wants to know the conditions related to the skill of speech, especially with regard to the way it is taught. The most appropriate model for the description process is the qualitative approach method, by means of the thesis or the case design. From this research, it is known that the teaching of speech skill uses several direct methods or oral auditory method of the communicative input. It is difficult to define a detailed definition of both methods if the term